CAUSES OF LOWER GASTROINTESTINAL BLEEDING ON COLONOSCOPY - Jehangiri, Attique-ur-Rehman; Gul, Rahaid; Hadayat, Rania; Khan, Adil Naseer; ., Zabiullah; Khursheed, Liaqat (Journal of Ayub Medical College Abbottabad, 2017)
Background: Rectal bleeding can refer to any blood that passes from the anus, although rectal bleeding is usually assumed to refer to bleeding from lower colon or rectum, which means bleeding from a place distal to ligament of Treitz. The estimated annual incidence rate is around 20.5 patients per 100,000; however, in individuals in the third to the ninth decades, the incidence rate of lower GI bleed increases more than 200-fold, and mortality due to lower GI bleed as 11%. Many modalities and investigations have been studied and proctosigmoidoscopy followed by colonoscopy is the investigation of choice for diagnosis and treatment for these patients. Previous studies suggested that in our country, frequencies of different aetiologies of lower GI bleed are different from the rest of the world, especially the west. This study validated the previous findings. The Objective of this study was to determine the frequency of different causes of rectal bleeding in patients at Ayub Teaching Hospital, Abbottabad. Methods: One hundred and nine patients with evidence of rectal bleed, without gender discrimination were selected by non-probability convenient sampling from the out-patient department and general medical wards. Patients with suspected upper GI source of bleeding; acute infectious bloody diarrhoea and any coagulopathy were excluded from the study. All patients were subjected to fibre-optic colonoscopy after preparation of the gut and findings were recorded. Where necessary, biopsy samples were also taken. Diagnosis was based on colonoscopic findings. Results: A total of 109 patients (57 males and 52 females) with mean age 35.81+19.18 yrs were part of the study. Colonoscopy showed abnormal findings in 91 (83.5%) patients. The commonest diagnosis was hemorrhoids, which was found in 23 (21.1%) patients. It was followed by inflammatory bowel disease (IBD) in 20 (18.3%) patients, solitary rectal ulcer in 9 (8.3%) patients and polyps in 9 (8.3%) patients. Other less frequent findings were non-specific inflammation and fungating growths in rectum. Conclusion: Colonoscopy can provide a visual diagnosis (e.g. ulceration, polyps) and grants the opportunity for biopsy or removal of suspected colorectal cancer lesions. Colonoscopy has a high diagnostic yield and is now the investigation of choice in patients presenting with bleeding per rectum. Hemorrhoids was the leading cause of bleeding per rectum in this study, followed by evidence of IBD while infrequent findings of polyps and diverticuli indicate that these are uncommon in this region. Key Words: Colonoscopy , Gastrointestinal Haemorrhage, Hemorrhoids Background: Bleeding from anus is usually referred as rectal bleeding but actually rectal bleeding is defined as bleeding from lower colon or rectum, which means bleeding from a place distal to ligament of Treitz. This study was conducted to determine the frequency of different causes of rectal bleeding in patients at Ayub Teaching Hospital, Abbottabad. Methods: One hundred and seventy-five patients with evidence of rectal bleed, without gender discrimination were selected by non-probability convenient sampling from the out-patient department and general medical wards. Patients with suspected upper GI source of bleeding; acute infectious bloody diarrhoea and any coagulopathy were excluded from the study. All patients were subjected to fibre optic colonoscopy after preparation of the gut and findings were recorded. Where necessary, biopsy samples were also taken. Diagnosis was based on colonoscopic findings. Results: A total of 175 patients (92 males and 83 females) with mean age 35.81±9.18 years were part of the study. Colonoscopy showed abnormal findings in 150 (85.7%) patients. The commonest diagnosis was haemorrhoids, which was found in 39 (22.3%) patients. It was followed by inflammatory bowel disease (IBD) in 30 (17.1%) patients, solitary rectal ulcer in 13 (7.4%) patients and polyps in 25 (14.3%) patients. Other less frequent findings were non-specific inflammation and fungating growths in rectum. Conclusion: Haemorrhoids was the leading cause of bleeding per rectum in this study, followed by evidence of IBD while infrequent findings of polyps and diverticuli indicate that these are uncommon in this region. Keywords: Colonoscopy; Gastrointestinal Haemorrhage; Haemorrhoids